Combined creatine and sodium bicarbonate supplementation enhances interval swimming - Mero, A. A.; Keskinen, K. L.; Malvela, M. T.; Sallinen, J. M. (The Journal of Strength and Conditioning Research, 2004)
This study examined the effect of simultaneous supplementation of creatine and sodium bicarbonate on consecutive maximal swims. Sixteen competitive male and female swimmers completed, in a randomized order, 2 different treatments (placebo and a combination of creatine and sodium bicarbonate) with 30 days of washout period between treatments in a double-blind crossover procedure. Both treatments consisted of placebo or creatine supplementation (20 g per day) in 6 days. In the morning of the seventh day, there was placebo or sodium bicarbonate supplementation (0.3 g per kg body weight) during 2 hours before a warm-up for 2 maximal 100-m freestyle swims that were performed with a passive recovery of 10 minutes in between. The first swims were similar, but the increase in time of the second versus the first 100-m swimming time was 0.9 seconds less (p < 0.05) in the combination group than in placebo. Mean blood pH was higher (p < 0.01-0.001) in the combination group than in placebo after supplementation on the test day. Mean blood pH decreased (p < 0.05) similarly during the swims in both groups. Mean blood lactate increased (p < 0.001) during the swims, but there were no differences in peak blood lactate between the combination group (14.9 ± 0.9 mmol·L-1) and placebo (13.4 ± 1.0 mmol·L-1). The data indicate that simultaneous supplementation of creatine and sodium bicarbonate enhances performance in consecutive maximal swims.